Significant Dark Current Suppression in Organic Photodetectors Using Side Chain Fluorination of Conjugated Polymer - Park, Byoungwook; Jung, Juhyoung; Lim, Dae Hee; Lee, Hanbee; Park, Sungjun; Kyeong, Minju; Ko, Seo Jin; Eom, Seung Hun; Lee, Seung Hoon; Lee, Changjin; Yoon, Sung Cheol (Advanced Functional Materials, 2022)
Dark current density (Jdark) is the most important factors determining signal-to-noise ratio, linear dynamic range and detectivity (D*) of organic photodetectors (OPDs). However, the solution-processed OPDs generally suffer from high Jdark under bias because the origin of Jdark still remains unclear and related to complicate factors. In this work, the effect of fluorinated alkyl side chain (FAC) of conjugated polymers (CPs) on the OPD performance is systematically investigated according to the number of fluorine atom. The OPDs, comprising the CPs with a FAC (CP-FAC), exhibit at least two orders lower Jdark (≈3.73 × 10-10 A cm-2 at -2 V) compared to that without FAC while significantly maintaining high external quantum efficiency (≈78%). This is because the side chain fluorination leads to the formation of a more ordered molecular structure of the CPs, which reduces the trap density and energetic disorder, thus resulting in the effective suppression of Jdark and in the enhancement of charge carrier mobility. The CP-FAC based OPD exhibits an exceptionally high D* (≈3.39 × 1013 cm Hz1/2 W-1 at -2 V) and a reasonable response speed (f-3db = ≈56.31 kHz). Furthermore, a photoplethysmography sensor comprising the CP-FAC based OPD in a transmission mode is demonstrated.
Keywords: Alkyl side chains; Dark current densities; Detectivity; Fluorinated side chains; High detectivity; Linear dynamic ranges; Low dark current; Organic photodetector; Organics; Side-chains